Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Cooperative Learning Tipe Stad di Kelas VII.1 SMPN 32 Tanjung Jabung Timur Semester Ganjil Tahun Pelajaran 2022/2023 - Marihot Pasaribu (Journal on Education, 2022)
This study aims to find out and discuss the learning outcomes of students' Mathematics using the STAD Type Cooperative Learning Model. This research is a type of classroom action research. The research was carried out in an odd semester of the 2022/2023 school year in class VII.1 of SMPN 32 Tanjung Jabung Timur with a total of 29 students. The research procedure is in two cycles. Each cycle consists of two meetings where each meeting includes planning, action, observation, and reflection. Data collection techniques with observation, documentation, and tests. Data analysis carried out in this study was percentage and data reduction. The results of this study indicate that the use of STAD-Type Cooperative Learning Model can improve mathematics learning outcomes in class VII.1 SMPN 32 Tanjung Jabung Timur